Phylogenetic and functional analysis of cyanobacterial Cytochrome c6-like proteins - Torrado, Alejandro; Iniesta-Pallarés, Macarena; Velázquez-Campoy, Adrián; Álvarez, Consolación; Mariscal, Vicente; Molina-Heredia, Fernando P. (Frontiers in Plant Science, 2023)
All known photosynthetic cyanobacteria carry a cytochrome c6 protein that acts transferring electrons from cytochrome b6f complex to photosystem I, in photosynthesis, or cytochrome c oxidase, in respiration. In most of the cyanobacteria, at least one homologue to cytochrome c6 is found, the so-called cytochrome c6B or cytochrome c6C. However, the function of these cytochrome c6-like proteins is still unknown. Recently, it has been proposed a common origin of these proteins as well as the reclassification of the cytochrome c6C group as c6B, renaming the new joint group as cytochrome c6BC. Another homologue to cytochrome c6 has not been classified yet, the formerly called cytochrome c6-3, which is present in the heterocyst-forming filamentous cyanobacteria Nostoc sp. PCC 7119. In this work, we propose the inclusion of this group as an independent group in the genealogy of cytochrome c6-like proteins with significant differences from cytochrome c6 and cytochrome c6BC, with the proposed name cytochrome c6D. To support this proposal, new data about phylogeny, genome localisation and functional properties of cytochrome c6-like proteins is provided. Also, we have analysed the interaction of cytochrome c6-like proteins with cytochrome f by isothermal titration calorimetry and by molecular docking, concluding that c6-like proteins could interact with cytochrome b6f complex in a similar fashion as cytochrome c6. Finally, we have analysed the reactivity of cytochrome c6-like proteins with membranes enriched in terminal oxidases of cyanobacteria by oxygen uptake experiments, concluding that cytochrome c6D is able to react with the specific copper-oxidase of the heterocysts, the cytochrome c oxidase 2.